2014
DOI: 10.1111/pace.12512
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Evidence for Epicardial Adipose Tissue: Heart Rate Variability and Turbulence are Influenced by Epicardial Fat Thickness

Abstract: Sympathovagal imbalance, detected by HRV and HRT parameters, is related to EAT thickness. As sympathovagal imbalance is a predictor of arrhythmic events, EAT may play an important arrhythmogenic role not limited to atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
2
27
0
2
Order By: Relevance
“…Third, increased epicardial fat thickness has been described in obese individuals 43 and has been associated with altered atrial electrophysiology 44 and sympathovagal imbalance of the atria. 45 In small case-control studies, increased epicardial fat has been associated with AF. 46, 47 …”
Section: Discussionmentioning
confidence: 99%
“…Third, increased epicardial fat thickness has been described in obese individuals 43 and has been associated with altered atrial electrophysiology 44 and sympathovagal imbalance of the atria. 45 In small case-control studies, increased epicardial fat has been associated with AF. 46, 47 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies show a close relation between epicardial fat and cardiac autonomic function [4][5][6]. It was shown that the cardiac ganglionated plexus in the epicardial fat integrates the autonomic innervation between the extrinsic and intrinsic cardiac autonomic nervous system and affects atrial electrophysiology and pathophysiology [4].…”
Section: To the Editorsmentioning
confidence: 99%
“…Additionally, Balcioglu et al showed that sympathovagal imbalance, detected by heart rate variability and turbulence parameters, is related to epicardial fat thickness. As sympathovagal imbalance is a predictor of arrhythmic events, epicardial fat may play an important arrhythmogenic role [6].…”
Section: To the Editorsmentioning
confidence: 99%
“…[19][20][21] Importantly, recent studies have also indicated a close relationship between EAT and myocardial autonomic function. 31,32 Many EAT-derived factors can directly modulate the electrophysiological properties and ion currents of myocytes and may promote arrhythmogenesis. 33 Moreover, EAT contains both adrenergic and cholinergic nerves which interact with the extrinsic SNS and para-SNS.…”
Section: Eat and Cardiac Sympathetic Denervationmentioning
confidence: 99%